Generation of Distinct Patterns of Rheumatoid Arthritis Autoantigens by Peptidylarginine Deiminase Types 2 and 4 During Perforin‐Induced Cell Damage. Issue 6 (7th April 2020) - Romero, Violeta; Darrah, Erika; Andrade, Felipe
Abstract : Objective: To address the independent roles of peptidylarginine deiminase type 2 (PAD2) and PAD4 in generating rheumatoid arthritis (RA) autoantigens by using a system that mimics intracellular citrullination in the RA joint. Methods: PAD2‐ or PAD4‐expressing 293T cells and mock‐transfected cells were used as targets in cytotoxic assays using lymphokine‐activated killer cells, cytotoxic YT cell granule contents, or purified human perforin. Protein citrullination and autoantigen production were determined by immunoblotting using the anti–modified citrulline–Senshu method and RA sera (n = 30), respectively. Results: RA sera recognized at least 3 categories of autoantigens in PAD‐expressing target cells killed by the cytotoxic lymphocyte granule–induced death pathway. These included: 1) autoantigens targeted in their native form, 2) citrullinated antigens, and 3) antigens cleaved by cytotoxic proteases (e.g., granzymes). Interestingly, although target cells expressing PAD2 or PAD4 showed prominent hypercitrullination of a broad range of proteins during cytotoxic granule–induced cell damage, autoantibodies in RA sera targeted only a very limited number of antigens in hypercitrullinated cells. Furthermore, RA sera showed distinct reactivities to autoantigens generated by PAD2 or PAD4. Conclusion: The cytotoxic granule–induced death pathway has the capacity to modify antigens by inducing hypercitrullination and antigen cleavage in target cells. Interestingly, among a large number of citrullinated proteins generated by PAD2 and PAD4 in cells, only a few are likely involved in the production of autoantibodies in RA.